2017
DOI: 10.1002/ptr.5838
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lepidium meyenii (Maca) Aqueous Extract and Lycopene on Testosterone Propionate-Induced Prostatic Hyperplasia in Mice

Abstract: The inhibitory effect of maca extractant, lycopene, and their combination was evaluated in benign prostatic hyperplasia (BPH) mice induced by testosterone propionate. Mice were divided into a saline group, solvent control group and testosterone propionate-induced BPH mice [BPH model group, solvent BPH model group, benzyl glucosinolate group (1.44 mg/kg), maca group (60 mg/kg), lycopene treated (15, 5, and 2.5 mg/kg), maca (30 mg/kg) combine lycopene treated (7.5, 2.5, and 1.25 mg/kg), and finasteride treated].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Control mice were administered the same volume of safflower seed oil (Sigma-Aldrich) at the same time. The doses of testosterone administration in this study were based on Zhao et al (2014), Ren et al (2017), andZou et al (2017) and the results of our preliminary experiment in the aorta.…”
Section: Administration Of Testosteronementioning
confidence: 99%
“…Control mice were administered the same volume of safflower seed oil (Sigma-Aldrich) at the same time. The doses of testosterone administration in this study were based on Zhao et al (2014), Ren et al (2017), andZou et al (2017) and the results of our preliminary experiment in the aorta.…”
Section: Administration Of Testosteronementioning
confidence: 99%
“…This is consistent with results of other works in which lycopene was used in several experimental BPH models. It was previously shown that lycopene isomers and lycopene in combination with Lepidium meyenii extract exert inhibitory effect on propionate‐induced BPH in mice (Zou et al., 2014, 2017). In addition, lycopene is effective in chemically induced prostatitis model through reduction in oxidative stress and inflammation pathways (Zhao et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A large group of natural compounds, including carotenoids, are used for BPH treatment or prophylaxis since they are quite effective and have low toxicity (Cicero et al., 2019). Among them, lycopene is one of the most promising agents as it is able to inhibit BPH both in the experiments and in patients (Dulińska‐Litewka et al., 2021; Zou et al., 2014, 2017). Still, its interaction with other supplementations which also have an inhibitory effect on BPH is poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…28 It also has adaptogenic effects, reducing stress-induced corticosterone levels, 29 and targets DHT. 30 Astaxanthin is an antioxidant 600-times more potent than vitamin C. It possesses anti-inflammatory and antioxidant properties, improving oxidative status overall and in aging skin. 31,32 In the current study, the daily use of this blend of nutraceutical-grade extracts significantly increased the number of terminal and vellus hairs in perimenopausal, menopausal, and post-menopausal women.…”
Section: Jo00121mentioning
confidence: 99%